Distinct Stromal and Immune Features Collectively Contribute to Long-Term Survival in Pancreatic Cancer - Sadozai, Hassan; Acharjee, Animesh; Eppenberger-Castori, Serenella; Gloor, Beat; Gruber, Thomas; Schenk, Mirjam; Karamitopoulou, Eva (Frontiers in Immunology, 2021)
Background: The aggressive biology and treatment refractory nature of pancreatic ductal adenocarcinoma (PDAC) significantly limits long-term survival. Examining the tumor microenvironment (TME) of long-term survivors (LTS) of PDAC offers the potential of unveiling novel biological insights and therapeutic targets. Methods: We performed an integrated approach involving immunophenotyping, stromal scoring and histomorphological profiling of a cohort of 112 PDAC-cases, including 25 long-term survivors (LTSs, OS≥60 months). Mutational frequencies were assessed using targeted next generation sequencing. Finally, we validated our findings in silico using an external cohort of microarray data from PDAC patients. Results: LTS-cases exhibit a largely quiescent population of cancer-associated fibroblasts (CAFs). Immune profiling revealed key differences between LTS and NON-LTS cases in the intratumoral and stromal compartments. In both compartments, LTS cases exhibit a T cell inflamed profile with higher density of CD3+ T cells, CD4+ T cells, iNOS+ leukocytes and strikingly diminished numbers of CD68+ total macrophages, CD163+ (M2) macrophages and FOXP3+ Tregs. A large proportion of LTS cases exhibited tertiary lymphoid tissue (TLT) formation, which has been observed to be a positive prognostic marker in a number of tumor types. Using a Random-Forest variable selection approach, we identified the density of stromal iNOS+ cells and CD68+ cells as strong positive and negative prognostic variables respectively. In an external cohort, computational cell-type deconvolution revealed a higher abundance of T cells, B lymphocytes and dendritic cells (DCs) in patients with long-term OS compared to short-term survivors. Thus, in silico profiling of long-term survivors in an external cohort, strongly corroborated the results from our cohort. Conclusions: Collectively, our findings highlight the prognostic importance of TME profiles in PDAC, underlining the crucial role of tumor associated macrophages (TAMs) and the potential interdependence between immunosuppressive TAMs and activated CAFs in pancreatic cancer. Additionally, our data has potential for precision medicine and patient stratification. Patients with a T cell inflamed TME might derive benefit from agonistic T cell antibodies (e.g. OX40 or CD137 agonists). Alternately, patients with activated CAFs and high infiltration of immunosuppressive TAMs are highly likely to exhibit therapeutic responses to to macrophage targeted drugs (e.g. anti-CSF1R) and anti-CAF agents.